Biochemical properties, nutritional quality, colour profile and techno‐functional properties of whole grain sourdough and malted cowpea and quinoa flours. (27th December 2021) - Kewuyemi, Yusuf Olamide; Kesa, Hema; Adebo, Oluwafemi Ayodeji
Abstract: The particular interest in biomodifications of underutilised but nutritionally distinct whole grains is vital to promote diet diversity, nutrition transition and food security. This study investigated the use of short‐term solid‐state fermentation and germination to ease processability and improve the quality characteristics of whole grain (WG) cowpea and quinoa flours. The fermented and germinated WG flours were prepared at 28 °C for 48 h. The biochemical, nutritional quality and techno‐functional properties of the obtained flours were determined. The macromolecules' biomodification by microbial metabolism and endogenous enzymes activation influenced quality variations in the biomodified flours. The cowpea sourdough flour (CSF) presented lower acidity (pH 4.72), higher total flavonoid (29.63 mg QE/g), total phenolic (8.21 mg GAE/g) and antioxidant activity. The flour also showed high contents of fibre (5.30%), ash (4.42%), calcium (864.49 mg/kg), potassium (12848.64 mg/kg), zinc (33.83 mg/kg), good protein (21.43%) and a moderate fat level (2.65%). Higher oil absorption and water solubility indices were also noted for CSF. In contrast, malted quinoa flour (MQF) exhibited higher swelling power, increased dispersibility and improved final, peak and trough viscosities. The CSF displayed higher redness and browning index, whereas MQF had greater lightness. The results suggest that CSF and MQF had the best complementary quality attributes. Their formulation as gluten‐free, whole and multigrain ingredients may promote healthy choices for individualised growing dietary needs.